Study of cucumber mosaic virus gene expression in Capsicum annuum - Azizan, Nur Hafizah; Zainal Abidin, Zulkifli Ahmad; Phang, Ing Chia (Zibeline International Publishing Sdn. Bhd., 2017)
Cucumber mosaic virus (CMV) is a plant pathogenic virus in the genus Cucumovirus, family Bromoviridae. It has the potential and reputation of having the widest host range of any known plant virus including monocotyledons and dicotyledons, herbaceous plants, shrubs and trees. CMV is one of the major diseases in Capsicum annum (chilli). Chilli plant samples exhibiting virus-like disease symptoms were collected from Taman Pertanian Indera Mahkota (location 1) and Greenhouse 12 of Horticulture Research Centre, Serdang (location 2). Viral disease was detected based on symptoms like mosaic-mottling, yellow ringspots and cholorotic that appeared on the leaves. The isolation of total RNA was done by using Vivantis GF-1 total RNA extraction kit. RT-PCR technique was used to detect the presence of virus disease symptoms gene in chillies. Identification of causal agents was based on cDNA amplified product size, using virus-specific oligonucleotides. Actin was used as the internal PCR control. The product size of the DNA fragment was 315 bp. From RT-PCR, the expression of CMV can be detected in chilli plants that exhibited the virus-like disease symptoms. This research revealed that some of the chilli plants at the Taman Pertanian Indera Mahkota and Greenhouse 12 of Horticulture Research Centre have been affected by this viral disease.